Os primeiros 62 AGNS observados com o SDSS-IV MANGA: cinemática estelar e do gás - Ilha, Gabriele da Silva (2018)
Active galaxies exhibit a great luminosity in central region that can not be explained only by the emission of the stars of the galaxy, but by the presence of an active galactic nucleus (AGN). In this scenario, gravitational potential energy is transformed into light energy during accretion of matter by a supermassive black hole on the so-called accretion disk, which is surrounded by a torus of gas and dust. The gas outflows are generated by the accretion disk and can be observed in the narrow-line region. Outflows can have an important impact on the host galaxy of the active nucleus. In this work, we have analyzed the impact of AGN feedback on the gas kinematics of a sample of 62 active galaxies. For this we have compared the kinematics of the active galaxy with two inactive galaxies that present the same characteristics of the host galaxy of the active nucleus, in other words, the same stellar mass, redshift, morphology and inclination. The sample of inactive galaxies (controls) have 109 galaxies. The objects of our sample were observed with integral field spectroscopy by the 2.5 meter Sloan telescope within the MaNGA survey that is part of SDSS-IV. We have performed the fitting of the galaxies observed spectra using the Gas AND Absorption Line Fitting routine, and have obtained the stellar and gas velocities fields , velocity dispersion and gas emission. Through the velocity fields we have determined the kinematic position angle (PA), in order to study the impact of AGN feedback on a galactic scale. We used the stellar velocity and gas dispersion to analyze the outflows on a smaller scale 2kpc. Comparing the difference between the PA orientation of the stellar velocity fields and the gas for the two samples, we found no clear difference between the distributions. On the other hand, the AGNs have greater difference in the fractional velocity dispersion sf rac between the gas and the stars when compared with controls. The mean value of sf rac for AGNs and controls is < sfrac >AGN= 0:04 and < sfrac >CTR= 0:23, respectively. Therefore, sf rac may be indicative of the presence of AGN. In addition, we found a positive correlation between the [O III]l5007 luminosity and sf rac for our sample. Our main conclusion in this work is that the outflows observed for the AGNs of our sample are not intense to interfere with the kinematics of the host galaxy on a large scale, but they have an important contribution on 2kpc scale.